Mitigation of Mach Zehnder modulator nonlinearity in millimeter wave radio over fiber system using digital predistortion - Duraikannan, Shankar (2017)
In this era of multiscreen generation, with connected devices per person escalating dramatically, the transmission of uncompressed videos and tons of data over wireless networks have driven the wireless networks to migrate from lower radio frequency to higher mm wave frequency band. The standard 802.11ad recommends the usage of 7 GHz unlicensed frequency spectrum at 60 GHz. The spectrum with low multipath impairment, suffers a high channel attenuation that demands mixed architecture of radio and fiber for enhancement of coverage distance. Radio over Fiber (RoF) using Mach Zehnder Modulator (MZM) is the most widely adapted architecture for mm-wave generation. However, the architecture with low insertion loss, power consumption, and dispersion effects suffers the effect of MZM nonlinearity that significantly limits the performance of RoF system.